Simplify 7 + [12 - {8 + 3 - (9 of 6 - 13 x 4 + 1)]].
Pls guys give me the answer step by step
Answers
Answered by
6
Answer:
here is your answer mark my answer as brainleast
Step-by-step explanation:
7+[12-{8+3-(9 of 6–13×4+1)}].
= 7+[12–{8+3–9 of 6 +13×4 - 1}].
= 7+[12- 8–3 + 9 of 6 - 13×4 +1 ].
= 7 +12–8 -3+ 9 of 6 -13×4 + 1.
= 7+12–8–3 +54 - 52 + 1.
=7+12+54+1–8–3–52
=74 - 63.
= 11. Answer
Second - Method :-
7+[12-{8+3-(9 of 6 -13×4 +1)}].
= 7+[12-{8+3-(54 -52+1)}].
= 7+[12–{8+3–3}].
= 7+[12–8].
= 7 +4.
= 11. Answer.
Answered by
0
Answer:
ANUBHAV
TH3 GAM3R
Step-by-step explanation:
HSBAUWU IS JSBSJSJAJANANJAAKJAJAJAJAHAHAHAHJjajajanananajansjjauajajakajsjksjajajajajanjajajajajajajjajajajajajajuajajauajajjauauahahsggajwiqowowowiwuuwowkebsbjskaowow
Similar questions